Relationship between Child Marriage and Stunting Incidence - Lidia Hastuti; Ridha Mardiyani; Abdu Samad; Dedy Purwanto; Wulan Masitha; Ika Laksita Dewi; Yudi Herdianto Wibowo (Indonesian Journal of Global Health Research, 2025)
Child marriage has a negative impact on the health of mothers and toddlers and can contribute to stunting. In reality, many women who marry at a young age and give birth under the age of 19 are mentally unprepared to face pregnancy, childbirth, and raising children. Objective: This study aims to find out the relationship between child marriage and stunting. This study uses a quantitative research design with a cross-sectional approach. The population in this study were married couples who already had children. The sample selection used an accidental sampling technique, with a sample size of 30 respondents. Data collection using questionnaires by research surveyors to collect primary data. Data analysis in this study used the chi-square test. Statistically, there is a significant relationship between child marriage and stunting incidence p=0.04 (p<0.05). Child marriage has a risk of 1.67 times having a child with stunting compared to marriage in adulthood (OR= 1.67, 95% CI 1.32-8.74). The level of maternal education is not related to the incidence of stunting p = 0.09 (p> 0.05). There is no relationship between maternal employment and the incidence of stunting p = 0.27 (p> 0.05), but the results of the estimation test show that mothers who do not work have a risk of 2.8 times stunted children compared to mothers who work (OR = 2.8, 95% CI 0.42-18.38). There is a relationship between the number of children and the incidence of stunting p = 0.04 (p <0.05). Mothers who have children > 2 are at risk of having stunted children compared to mothers who have children ≤2 (OR = 2.17, 95% CI 1.43-3.28). Anemia in mothers during pregnancy is not related to the incidence of stunting with a value of p = 0.35 (p> 0.05). There is a significant relationship between early marriage, the number of children, and the incidence of stunting. The level of education, employment, and anemia status in mothers during pregnancy are not related to the incidence of stunting.